2020
DOI: 10.13106/jafeb.2020.vol7.no6.399
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Expectations and Social Entrepreneurial Intention: Integration of Planned Behavior and Social Cognitive Career Theory

Abstract: The paper examines social entrepreneurial intention through outcome expectations. The proposed model incorporates outcome expectations from social cognitive career theory and theory of planned behaviors. The study also introduces a scale for outcome expectations in social entrepreneurship, including solving social problems, innovation, family tradition of social involvement, meaning in life, prestige and social recognition, competitive and favorite job and wealth. A survey of 279 students was conducted through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 54 publications
7
35
2
2
Order By: Relevance
“…Many scholars concluded that entrepreneurial intention can produce new entrepreneurs but in reality, the number of new entrepreneurs, especially in developing countries is still very low (Phan, 2018). Having said that, they still agree that entrepreneurial intention is still the best indicator for creating a new business (Ajzen, 1991;Ajzen, 2002;Linan & Chen, 2009;Luc, 2020).…”
Section: Literature Review and Hypohtesismentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars concluded that entrepreneurial intention can produce new entrepreneurs but in reality, the number of new entrepreneurs, especially in developing countries is still very low (Phan, 2018). Having said that, they still agree that entrepreneurial intention is still the best indicator for creating a new business (Ajzen, 1991;Ajzen, 2002;Linan & Chen, 2009;Luc, 2020).…”
Section: Literature Review and Hypohtesismentioning
confidence: 99%
“…It directs the work of individuals' minds, experiences, skills, actions, and goals toward everything related to entrepreneurship (Fini et al, 2012;Vamvaka et al, 2020). With entrepreneurial intention, it will help entrepreneurs to be able to understand and plan a new business (Luc, 2020) because the ability needed to be an entrepreneur is not only based on the knowledge and cognitive aspects . The factors that influence entrepreneurial intentions are many, but on this research the main factors are based on the theory of planned behavior (Ajzen, 1991;Zhang et al, 2019).…”
Section: Literature Review and Hypohtesismentioning
confidence: 99%
“…The company's business performance is one of the goals of every entrepreneur (Luc, 2020). The performance of a company's business can be interpreted as the level of success in achieving the intended targets or objectives.…”
Section: Resultsmentioning
confidence: 99%
“…Intersubjectivity is a common understanding or experience between subjects (informants). A person's perception is considered objective if several subjects have the same view of the observed object, then there is an intersubjective relationship to determine the objectivity (Luc, 2020). The others interview with respondents stated that they interpret success when they are useful to others as they said:…”
Section: Useful To Othersmentioning
confidence: 99%
“…How individuals perceive the consequences of their actions inform and change both their perception of their environment and the cognitive factors (e.g., domain-specific, self-efficacy, etc. ); they can, thus, alter their actions (Luc, 2020).…”
Section: Bandura' Career Theorymentioning
confidence: 99%